(untitled) (African Human Mobility Review, 2025)
In the midst of closure and securitization of border regimes, climate-change displacement, and entrenched inequalities, migrant communities are not just surviving but creating new sites of resistance, creativity, and adaptation to their worlds in crisis. This paper explores how migrant-solidarity organizations function as epistemic spaces of invention and resistance in South Africa among Zimbabwean, Pakistani, and Cameroonian migrant communities in Parow Valley, Summer Greens, and Kensington (Cape Town). Based on 250 household surveys and 12 qualitative in-depth interviews, the paper explores how migrant-led social movements become sites of agency, social resilience, and resistance to marginalization habitually employed by state policy and academic scholarship. These forms of solidarity networks, which are essentially national in scope, maintain food security at a household level, access to livelihood, and socioemotional well-being. Group savings, mutual support, and rotating credit associations enable these networks to build adaptive capacities to deal with uncertain migration status and socio-economic risk. They constitute resilient, informal social safety nets for food, income, and affective resources that go beyond what formal mechanisms can provide. By situating migrant practice and epistemologies, the paper challenges hegemonic discourses that position migrants as passive. Instead, it positions everyday solidarities at the site of politicized invention and resistance. It situates where these practices intersect with Sustainable Development Goal (SDG) 2 (zero hunger), SDG 8 (decent work), and SDG 10 (reduced inequalities). It establishes a decolonial, plural migration knowledge positioning migrants as co-producers, policy entrepreneurs, and change agents.